Arsitektur Bagas Godang di Desa Huta Godang, Kecamatan Ulu Pungkut, Kabupaten Mandailing Natal - Jambak, Reni Angraini; Achiriah, Achiriah; Devianty, Rina (Medan Resource Center, 2024)
This research focuses on the history and architecture of Bagas Godang in Huta Godang Village, Ulu Pungkut Sub-district, Mandailing Natal Regency, and the meaning of its ornaments. The purpose of this research is to understand the historical background and architectural details of Bagas Godang and the meaning of the various ornaments contained in it. The method used is descriptive qualitative, with data collection through direct observation, interviews, and analysis of documents, books, photos, and videos. The results showed that the current Bagas Godang is the second building built by King Junjungan Lubis and the people of Huta Godang, after the previous building burned down without knowing when exactly the event occurred. Bagas Godang is characterized by Mandailing architecture with wooden construction, rectangular in shape, supported by an odd number of large timbers, and consists of a vestibule, living room, sleeping room, and kitchen. The roof is in the form of a dolok-arched tarup, with a wide door that makes a loud sound when opened. There are 26 types of ornaments that reflect traditional symbols and create an official agreement on the decoration of Mandailing traditional houses. This research provides an in-depth insight into Mandailing's cultural heritage and traditional architecture.